The Influence of the Policies of the Russian Empire and Colonial Administration in the Agricultural Sector in the Country of Turkeston on the Vaqf Properties (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article provides information about the impact of the policy of the Russian Empire and the colonial administration on the agrarian sector in Turkestan, the legal basis of this policy, the liquidation of the foundation properties, and their transformation into state property. In addition, the main goal of the colonial administration to end the endowment was also highlighted. Also, registration of 212 madrassas in Turkestan by the General Vaqf Department, and their gradual closure. It is reported that their buildings were adapted to new Soviet schools, religious subjects were completely removed from the curriculum of madrasahs, and historians' research on this topic.